Theoretical principles relevant to assessment center design and implementation - THORNTON, George C. (Institutional Knowledge at Singapore Management University, 2018)
Decades ago, assessment centers (Acs) originated by applying the best available evidence and theory to the assessment of managerial performance dimensions. The objectives of this chapter are to take stock of these existing theoretical principles, present additional theoretical principles that have emerged in recent times, and describe the practical implications of these principles for effective Ac design and implementation. Thus, while all Acs include several essential elements, developing and implementing a specific Ac involves a complicated set of choices. This chapter shows how these choices can be guided by theories relevant to the Ac method as a whole and each of its essential elements. The chapter is quite timely, because of research findings questioning the validity and fairness of Acs and practical pressures to streamline the process. Furthermore, the chapter is the first to explicate the applications of these several theories in one source.